From preventive to permissive checks: the changing nature of the Malthusian relationship between nuptiality and the price of provisions in the nineteenth century - Sharp, P; Weisdorf, J (University of Oxford, 2007)
The Malthusian "preventive check" mechanism has been well documented for pre-industrial England through evidence for a negative correlation between the marriage rate and the price of wheat. Other literature, however, speculates that the correlation was in fact positive from the early nineteenth century. This paper uses the cointegrated VAR model and recursive estimation techniques to document the changing relationship between nuptiality and the price of wheat from 1541-1965. The relationship is indeed positive from the early nineteenth century to the First World War. A simple theoretical model shows that this result is not in fact inconsistent with a stylized Malthusian mechnanism, and can be understood within the context of an increasing dominance of shocks to aggregate demand rather than to aggregate supply.